Application of zero waste farming system technology for the empowerment of farmers and breeders in Sigi Regency, Central Sulawesi - Hasriyanty Hasriyanty; Burhanuddin Haji Nasir; Sulaeman Sulaeman; Sri Anjar Lasmini (Universitas Muhammadiyah Magelang, 2024)
The Covid-19 pandemic affects all sectors, including agriculture. Challenges faced by the